Digital Transformation in Tourism Village Governance: A Case Study of Nusa Village Using IPA and ANOVA - Ahlul Ipdana Fikri; Friesca Erwan; Nur Izzaty (Journal of Aceh Studies, 2025)
Background of the problem: The incorporation of digital technologies in rural tourism governance is essential for improving transparency, efficiency, and community involvement. Desa Wisata Nusa, situated in Aceh Besar, Indonesia, exemplifies a tourism town with significant potential for digital transformation under the Smart town paradigm. Purpose: This study seeks to evaluate the degree of digitalization in the governance of Nusa Tourism Village by examining stakeholder perspectives across three dimensions: Smart Governance, Smart Society, and Smart Economy. Method: A mixed-method approach was utilized, gathering data from 50 respondents embodying the Penta helix paradigm, which encompasses academics, business, community, government, and media. The research employed Importance Performance Analysis (IPA) to pinpoint areas necessitating enhancement and Analysis of Variance (ANOVA) to investigate perceptual disparities among stakeholder groups. Result: The findings reveal considerable differences in stakeholder perceptions across all parameters. The preparedness of the workforce for digital tourism has become a crucial issue necessitating urgent focus. Conversely, elements like digital marketing, operational efficacy, and availability of digital educational resources were seen as operating satisfactorily and should be preserved. Implication: The results underscore the significance of focused capacity enhancement and reinforced multi-stakeholder collaboration to facilitate sustainable digital governance in tourism communities. These results enhance the wider discussion on rural digitalization and provide actionable consequences for policy formulation and execution.